General Orders of the Board of Supervisors Providing Regulations for the Government of the City And County of San Francisco: Also, Ordinances of Park Commissioners 8 (1884) - (:unkn) unknown (My University, 1880)
General Order no. 1,603-Relating to the Police Department, § 22-Prohibiting the Carrying of Concealed Deadly Weapons. Approved September 17, 1880: Prohibited the concealed carry of any pistol, dirk, or dangerous or deadly weapon.
Keywords: CARRY - CONCEALED